Correlation of E-cadherin Expression in Endometrial Carcinoma with Tumour Grade and Stage - RH, Lizawati; Sabrina TL, Nur Maya; MS, Muhammad Fakhri; AS, Nordashima; MN, Azmawati (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Endometrial carcinoma (EC) is among the common malignancy in the female with adverse prognosis in the advanced stage. Prediction of its prognosis is important in stratifying EC patients to achieve optimum treatment and improve clinical outcomes. This study is aimed to evaluate the prognostic significance of E-cadherin expression in patients with EC. The present study also investigated the correlation of E-cadherin expression in EC with its tumour grade and stage. MATERIALS AND METHODS: A total of 70 cases of EC were included in the study within eleven years comprising 56 cases of endometrioid carcinoma, 2 cases of mucinous carcinoma, 10 cases of serous carcinoma and 2 cases of clear cell carcinoma. E-cadherin expression was immunohistochemically analysed and compared with clinicopathological parameters. RESULTS: E-cadherin loss of expression shows significant association with non endometrioid EC (p=0.003), high tumour grade (p<0.001) and tumour with distant metastasis (p=0.028). Tumour grade is the main predictor of down-regulation of E-cadherin expression (Grade 3: aOR 8.400, 95%CI 2.534-27.842). There was no significant association found between E-cadherin expression with myometrial invasion, FIGO stage, lymph node status and lymphovascular invasion. CONCLUSION: E-cadherin loss of expression correlates with poor prognostic factors namely high grade and high stage (metastasis) EC. This may serve as a potential prognostic marker for EC>< 0.001) and tumour with distant metastasis (p=0.028). Tumour grade is the main predictor of down-regulation of E-cadherin expression (Grade 3: aOR 8.400, 95%CI 2.534-27.842). There was no significant association found between E-cadherin expression with myometrial invasion, FIGO stage, lymph node status and lymphovascular invasion.